Ag NPs decorated on a COF in the presence of DBU as an efficient catalytic system for the synthesis of tetramic acids via CO2 fixation into propargylic amines at atmospheric pressure. Issue 14 (20th March 2019) - Ghosh, Swarbhanu; Molla, Rostam Ali; Kayal, Utpal; Bhaumik, Asim; Islam, Sk. Manirul
Abstract : Ag NPs are decorated at the surface of a COF material TpPa-1 and the resulting Ag@TpPa-1 catalyzes efficiently for the synthesis of tetramic acids from a variety of propargylic amines using CO2 as reagent. Abstract : CO2 fixation reactions by inserting it in reactive organic compounds are very challenging for the utilization of this abundant and harmful gas present in air and thus to mitigate this greenhouse gas responsible for global warming. This can be achieved by appropriate design of functionalized porous nanocatalysts having high surface areas and porosity and good CO2 uptake capacity. Herein, we first report the decoration of silver nanoparticles (NPs) over the surface of a covalent organic framework (COF) material TpPa-1 synthesized through the polycondensation of 2, 4, 6-triformylphloroglucinol (TFP) and p -phenylenediamine. The resulting material Ag@TpPa-1 was thoroughly characterized by N2 adsorption/desorption, powder X-ray diffraction (PXRD), FE-SEM, TEM, UV-Vis, FT IR and thermogravimetric techniques. This Ag NP decorated porous COF in the presence of DBU exhibited excellent catalytic activity for the synthesis of tetramic acids from a variety of propargylic amine derivatives at 60 °C under atmospheric pressure of carbon dioxide via formation of oxazolidinones, where CO2 acts as a C1 reagent. The Ag@TpPa-1 catalyst exhibited excellent recycling efficiency for the synthesis of tetramic acid with no leaching of Ag from the catalyst surface.